Energy Efficiency as Green Campus Development from IIUM Academicians Perspective - Nursulistiyo, Eko; Pramudyani, Avanti Vera Risti; Indratno, Toni Kus; Asmorojati, Anom Wahyu (Indonesian Review of Physics, 2024)
Green Campus is an important program to solve environmental problems. One part of Green Campus is energy efficiency on campus. This study aims to determine the implementation and knowledge of green campus policies at IIUM through a survey of IIUM academicians. The results of the energy efficiency survey data analysis showed that students, lecturers, and staff at IIUM have been Good in the efficiency of using lights (80.59%), quite good in the efficiency of using AC (68.82%), quite good in knowing the implementation of energy efficiency by IIUM (64.12%), and quite knowledgeable about the energy efficiency management system and its monitoring (60.59%). Based on these results, it is necessary to improve understanding, socialization, and implementation of energy efficiency programs on campus accompanied by monitoring